Developing employee’s technical skills: the relationship between training effectiveness and employees performance at Menara MSC Cyberport Johor / Mohd Khairul Akmal Mohd Dzahir and Nur Zawanah Mansor - Mohd Dzahir, Mohd Khairul Akmal; Mansor, Nur Zawanah (Faculty of Business and Management, 2014)
Project paper titled “ Developing employee‘s technical skills: the relationship between training effectiveness and employees performance” is conducted as partial requirement as needed by the Faculty of Business Management, University Technology of MARA (UiTM). The intention of this study is to identify the most factors that affecting the job performance among employees in the Menara MSC Cyberport Johor Bahru as the scope study in this research and the significant relationship between factors influencing their job performance. The researcher chooses to use descriptive research design as a method and the researcher use survey in order to gain the data. Data used in this research are primary and secondary data such as journal, websites and books. Researcher also use questionnaires to attain data in order to get the feedback from the employees at Menara MSC Cyberport Johor Bahru. The sample size in this research is 100 respondent of employee from different companies inside Menara MSC Cyberport Johor Bahru. Based on reliability test, respondent profile, frequency, Pearson correlation and multiple regressions, a clear findings and result is observed. The finding showed that most of the employee have moderate of effectiveness of training with the trainer‘s skills and superior supports while employee‘s motivation, and training environment show the low correlation on effectiveness of training. Other than that, trainer‘s skills have high correlation with effectiveness of training if compared other independent variables. The researcher is also able to give some recommendations and suggestion on how to improve and increase job performance of the employee‘s after analysis, findings and interpretation. The conclusion of this study was the outcome from the survey analysis and findings.